2022
DOI: 10.3389/fonc.2022.995991
|View full text |Cite
|
Sign up to set email alerts
|

Association of neutrophil-lymphocyte ratio, platelet-lymphocyte ratio, and De Ritis ratio with mortality in renal cell carcinoma: A multicenter analysis

Abstract: BackgroundSeveral markers of inflammation have been associated with oncologic outcomes. Prognostic markers are not well-defined for renal cell carcinoma (RCC). We sought to investigate the association of preoperative neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and De Ritis ratio with mortality in RCC.MethodsMulti-center retrospective analysis of patients undergoing surgery for RCC. Primary outcome of interest was all-cause mortality (ACM). Secondary outcomes were non-cancer mortality (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…32 In a multicenter study, Keiner et al found that elevated NLR was independently associated with worsening of all-cause mortality (ACM) and noncancer mortality (NCM) in RCC patients, whereas elevated De Ritis could predict cancer-specific mortality (CSM) in addition to ACM and NCM. 33 In addition, the novel blood indicator F-NLR combining preoperative plasma fibrinogen and NLR proved to be a novel and effective prognostic biomarker for RCC patients undergoing laparoscopic nephrectomy. 34 New combinations based on absolute number of preoperative lymphocyte, monocyte, and neutrophil counts have been constructed and demonstrated to be prognostic indicators for colorectal cancer patients.…”
Section: Characteristicsmentioning
confidence: 99%
“…32 In a multicenter study, Keiner et al found that elevated NLR was independently associated with worsening of all-cause mortality (ACM) and noncancer mortality (NCM) in RCC patients, whereas elevated De Ritis could predict cancer-specific mortality (CSM) in addition to ACM and NCM. 33 In addition, the novel blood indicator F-NLR combining preoperative plasma fibrinogen and NLR proved to be a novel and effective prognostic biomarker for RCC patients undergoing laparoscopic nephrectomy. 34 New combinations based on absolute number of preoperative lymphocyte, monocyte, and neutrophil counts have been constructed and demonstrated to be prognostic indicators for colorectal cancer patients.…”
Section: Characteristicsmentioning
confidence: 99%